Interações medicamentosas em pessoas idosas com diabetes : um censo populacional - Botesini, Gabriele da Graça (2025)
Diabetes Mellitus (DM) is often associated with the presence of multimorbidities and, as a consequence, individuals with DM become the population group with the highest medication consumption. This situation increases the likelihood of drug interactions and places these individuals at greater risk of hypoglycemia. In this context, the present study aimed to analyze medication use and associated factors among community-dwelling older adults with DM. This is a crosssectional, census-based study involving individuals aged 60 years or older residing in the municipality of Coxilha, in the state of Rio Grande do Sul (RS), Brazil. The database was built using data collected from August to December 2021. Data collection was carried out through home interviews using a standardized and pre-coded questionnaire. The outcome, use of Potentially Inappropriate Medications (PIMs), was assessed based on the medications used, according to two explicit criteria lists for PIM evaluation: the Beers Criteria (2023 version) and the Brazilian Consensus on Potentially Inappropriate Medications for Older Adults (CBMPI) (2016 version). For the outcome of drug interactions (DIs), interactions were classified by severity according to the website Drugs.com. Descriptive and inferential statistics were employed for the analysis. Qualitative variables (categorical, nominal, and ordinal) were presented using univariate frequency distributions (absolute and relative), as well as bi- and multivariate contingency tables. Quantitative variables were described using measures of central tendency (mean and median) and variability (standard deviation, 25th and 75th percentiles, minimum, and maximum). To assess the association between categorical variables, Pearson’s chi-square test, Fisher’s exact test, and the linear trend test were applied in the crude analysis, and Poisson regression models with robust variance were used in the adjusted analysis, with effect measures expressed as Prevalence Ratios (PRs) and respective 95% Confidence Intervals (95% CIs). A significance level of 5% was adopted. Variables with p ≤ 0.20 were considered for inclusion in the multiple regression model. There was a significant association between the presence of severe DIs and female sex (p = 0.044), as well as the presence of polypharmacy (p = 0.009). Regarding PIM use, 77.3% of older adults used at least one PIM according to the Beers Criteria (2023), and 76.5% according to the CBMPI (2016), with good agreement between the two tools. Approximately half of the participants exhibited cognitive decline according to the Mini-Mental State Examination (MMSE) cut-off scores, and this remained associated with PIM use in both crude and adjusted analyses for sociodemographic and clinical variables. The findings reinforce the need for intersectoral strategies to promote the rational use of medications in primary care, with emphasis on professional training and pharmacotherapeutic monitoring of older adults with DM. The comparison between the criteria revealed good agreement but highlighted the need to revise and update the Brazilian criteria to align with current evidence and the national context. Establishing a national database of drug interactions and adopting specific screening tools may contribute to safer practices for older adults.